2016
DOI: 10.2196/games.6448
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Resuscitation Training by Avatars: A Qualitative Study of Medical Students’ Experiences Using a Multiplayer Virtual World

Abstract: BackgroundEmergency medical practices are often team efforts. Training for various tasks and collaborations may be carried out in virtual environments. Although promising results exist from studies of serious games, little is known about the subjective reactions of learners when using multiplayer virtual world (MVW) training in medicine.ObjectiveThe objective of this study was to reach a better understanding of the learners’ reactions and experiences when using an MVW for team training of cardiopulmonary resus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…For example, VR can be used to train clinicians in complex procedures such as transvenous lead extraction, is effective in cardiopulmonary resuscitation training, can improve communication skills, enhance critical thinking and improve clinical decision making. [15][16][17][18][19] VR has also been favourably tested against physical simulation. In one paper, 84 nursing students were randomised to either a virtual or physical nursing simulation.…”
Section: Does Vr Simulation Work?mentioning
confidence: 99%
“…For example, VR can be used to train clinicians in complex procedures such as transvenous lead extraction, is effective in cardiopulmonary resuscitation training, can improve communication skills, enhance critical thinking and improve clinical decision making. [15][16][17][18][19] VR has also been favourably tested against physical simulation. In one paper, 84 nursing students were randomised to either a virtual or physical nursing simulation.…”
Section: Does Vr Simulation Work?mentioning
confidence: 99%
“…Although past studies have found that AV feedback can improve CPR quality (18), the additional application of the AR technology to overlay a holographic image of the circulatory system, which is responsive to the quality of CPR being performed, is novel. While studies have found that using immersive technologies similar to AR, such as virtual reality, can improve trainee experience and confidence, to our knowledge, no studies have linked these technologies with outcomes (19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 96%
“…Lifesaver [61] HeartSaver [62] LISSA [63,64] FujiokaGame [65] LISSA Kinect [66,67] OakGame [68] MarchioriGame [69] LamboyGame [70] MVW [71][72][73][74][75][76][77][78] From the analized games, 95% were classified as digital and based on simulation. Only 19% of games have external hardware, these are the ones that allow the user to practice compression depth with a physical interface.…”
Section: Methodsmentioning
confidence: 99%